Granularity in Banking and Growth: Does Financial Openness Matter? - Franziska Bremus; Claudia M. Buch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
We explore the impact of large banks and of financial openness for aggregate growth. Large banks matter because of granular effects: if markets are very concentrated in terms of the size distribution of banks, idiosyncratic shocks at the bank-level do not cancel out in the aggregate but can affect macroeconomic outcomes. Financial openness may affect GDP growth in and of itself, and it may also influence concentration in banking and thus the impact of bank-specific shocks for the aggregate economy. To test these relationships, we use different measures of de jure and de facto financial openness in a linked micro-macro panel dataset. Our research has three main findings: First, bank-level shocks significantly impact on GDP. Second, financial openness lowers GDP growth. Third, granular effects tend to be stronger in financially closed economies.
urn:nbn:de:gbv:3:2-23723
Keywords: G21; E32; 330; bank market structure; financial openness; granular effects; growth